Corporate Social Responsibility, Firm value and the Moderating effect of Government Ownership: Evidence from Viet Nam - Hang Thi Thuy Pham; Jung-Sung Chang; Su-Yol Lee (My University, 2019)
Corporate Social Responsibility, Firm value and the Moderating effect of Government Ownership: Evidence from Viet Nam
Keywords: CSR; Firm value; Government ownership